ON THE EDGE VERSION OF GEOMETRIC-ARITHMETIC INDEX OF NANOCONES - NADEEM, Muhammad Faisal; ZAFAR, Sohail; ZAHID, Zohaib (Studia Universitatis Babeș-Bolyai Chemia, 2016)
In this paper, the edge version geometric-arithmetic index of certain nanocones is presented.